Quality Management Analysis Using Seven Tools Case Study of Tinumpuk Tempe Factory - Faqih, Abu Rizal; Miharja, Rediawan (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Tempeh is a traditional food typical of Indonesian society. Tempe is in demand by the public not only because of its affordable price, but also because it has a variety of flavors and presentation variations that make it popular from the middle to upper economic class. In recent years, tempeh has also received international attention as a healthy food. However, quality issues are often an obstacle for micro, small and medium enterprises (MSMEs). This study uses quantitative methods to analyze the quality factors of soybean tempeh manufacturing by applying the concept of quality management through seven tools. The results of the analysis show that quality problems in the tempeh production process are black or brown tempeh, consumers do not take orders, soybeans are not washed thoroughly, and the beans are too fluffy. Improvements needed in the production process, selection of quality raw materials, and improvement of employee skills can be the first step to improve the quality of tempeh products. Quality control of tempeh production is expected to have a positive impact, especially in reducing the number of black or brownish tempeh, as well as increasing customer satisfaction.